KEPRIBADIAN MUSLIM YANG BAIK DALAM SUROH AL-FURQON AYAT 63-75 - Daulae, Tatta Herawati (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
The Koran is the first source in Islamic teachings handed down to the Prophet Muhammad, whose contents contain three points, namely the issue of faith, Shari'a and the story of one of the surrender in the Qur'an is Suroh Al-Fur'qon. In suroh al-furqon verses 63-75 tell the characteristics of a good Muslim personality that is walking humbly, when talking to people who do not know, he speaks safely (if people curse him badly he does not return badly but he forgives him), the person who is always awake at night, has fear of the fire of hell, always prays to avoid him, has a sense of generosity, does not associate with God, does not commit murder, does not commit adultery, always repent, always improves faith and acts pious, do not want to give false testimony (lie), do not do in vain, people who are ready to receive a good warning, people who always beg to be given family and descendants who can calm hearts and be a good example for others and have patience